Do not rush for surgery; stent placement may be an effective step for definitive treatment of initially unextractable common bile duct stones with ERCP - GÜNAL, ÖMER (SPRINGER, 2016)
Endoscopically unextractable common bile duct stones may be challenging for the endoscopist. In this study, we investigated the rate of stone removal after the endoscopic insertion of a biliary stent in patients with common bile duct stones unextractable via ERCP. Records of patients with common bile duct stone/s who underwent ERCP at single center were retrospectively analyzed. Only patients with common bile duct stone/s who had a stent placed due to unyielding stone removal were eligible for inclusion into this study. Endoscopic biliary stents were placed in cases of unextractable stone. After a follow-up period, a second ERCP procedure was performed. Major outcomes were the rate of stent insertion because of unextractable bile duct stones, the rate of spontaneous stone passage and the rate of stone extraction after the endoscopic insertion of a biliary stent. A total of 66 (28 %) patients had a stent placed due to unyielding attempts for stone removal, and 43 patients were included in the study. The second ERCP procedure revealed that 10 patients (23 %) had spontaneous stone passage and 5 (12 %) had spontaneous passage of both the stone and the stent. In the second procedure, biliary balloon was used successfully to extract the retained stone in 22 (51 %) patients. Thus, a total of 37 patients (86 %) with retained stones had a successful stone extraction during the second ERCP procedure. Biliary stenting may be an effective step for definitive treatment of initially unextractable common bile duct stones with ERCP.
Keywords: Choledocholithiasis; ERCP; Biliary stenting; LONG-TERM TREATMENT; ELDERLY-PATIENTS; BALLOON DILATION; CHOLEDOCHOLITHIASIS; SPHINCTEROTOMY; ENDOPROSTHESIS; MANAGEMENT; EFFICACY